2022
DOI: 10.3389/fphar.2022.959074
|View full text |Cite
|
Sign up to set email alerts
|

Targeted bile acid profiles reveal the liver injury amelioration of Da-Chai-Hu decoction against ANIT- and BDL-induced cholestasis

Abstract: Multiple types of liver diseases, particularly cholestatic liver diseases (CSLDs) and biliary diseases, can disturb bile acid (BA) secretion; however, BA accumulation is currently seen as an important incentive of various types of liver diseases’ progression. Da-Chai-Hu decoction (DCHD) has long been used for treating cholestatic liver diseases; however, the exact mechanisms remain unclear. Currently, our study indicates that the liver damage and cholestasis status of the α-naphthylisothiocyanate (ANIT)-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 85 publications
0
8
0
Order By: Relevance
“…46 TUDCA is a derivative of UDCA that enhances the ability to promote the hydrophilic conversion of bile pools and protects hepatocytes and cholangiocytes. 47 ANIT induced remarkable increases in total, unconjugated, glycine-conjugated, and taurine-conjugated BAs, and triptolide induced significant increases in total and taurine-conjugated BAs. An increase in conjugated BAs contributes to BA excretion and inhibition of liver injury.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…46 TUDCA is a derivative of UDCA that enhances the ability to promote the hydrophilic conversion of bile pools and protects hepatocytes and cholangiocytes. 47 ANIT induced remarkable increases in total, unconjugated, glycine-conjugated, and taurine-conjugated BAs, and triptolide induced significant increases in total and taurine-conjugated BAs. An increase in conjugated BAs contributes to BA excretion and inhibition of liver injury.…”
Section: Discussionmentioning
confidence: 88%
“…An increase in conjugated BAs contributes to BA excretion and inhibition of liver injury. 48 The levels of taurine-conjugated BAs in mice are predominant in the liver and are more sensitive to cholestasis, 47 with the most significant increase seen upon ANIT and triptolide treatment. In contrast, CXCR3 knockout mice did not show significant changes in the BA pool size or the aforementioned BAs after administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various liver conditions, including cholestasis and biliary diseases, may interfere with BA secretion. Nevertheless, it is now understood that the accumulation of BAs in the hepatocytes can exacerbate multiple liver diseases (Zhou et al, 2022). In recent years, targeted metabolomics has gained importance in drug metabolism, therapeutic actions, toxicity, and the regulation of BA metabolism (Liu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that DCHD exhibits beneficial effects on protecting the liver, cholagogic action, anti-inflammation, and regulating glucose and lipid metabolism. [53] In the research, it was effective in ameliorating pancreatic fibrosis by inhibiting macrophage infiltration and inflammatory factor secretion in the pancreas, [54] and inhibiting the activation of the transforming growth factor (TGF)-β/ Smad signaling pathway. [55] Meanwhile, the accessory use of DCHD on conventional Western medical treatment can strikingly shorten the course of AMP.…”
Section: Dachengqi Decoctionmentioning
confidence: 99%